A heterogeneous gold(I)-catalyzed ring expansion of unactivated alkynylcyclopropanes with sulfonamides leading to (E)-2-alkylidenecyclobutanamines. Issue 39 (28th September 2016) - Yi, Feiyan; Huang, Bin; Nie, Quan; Cai, Mingzhong
Graphical abstract: A novel, efficient, and practical heterogeneous gold(I)-catalyzed ring expansion of unactivated alkynylcyclopropanes to ( E )-alkylidenecyclobutanamines in the presence of sulfonamides have been described. Highlights: The new Fe3 O4 @SiO2 -P-AuOTf complex can be easily prepared by a simple procedure. Heterogeneous Au-catalyzed ring expansion of alkynylcyclopropanes is first reported. The reaction generates ( E )-2-alkylidenecyclobutanamines in moderate to high yields. The Au(I) catalyst can be recycled for 10 times without a significant loss of activity. Our catalytic system provides a new and practical route to four-membered carbocycles. Abstract: A heterogeneous gold(I)-catalyzed ring expansion of unactivated alkynylcyclopropanes was achieved in 1, 2-dichloroethane at 100 °C in the presence of sulfonamides by using a magnetic nanoparticle-supported phosphine gold(I) complex [Fe3 O4 @SiO2 -P-AuOTf] as catalyst, yielding a variety of ( E )-2-alkylidenecyclobutanamines in moderate to high yields. The new heterogeneous gold catalyst can easily be separated from the reaction mixture by applying an external magnet and recycled at least 10 times without a significant loss of activity.